Estrategias bioclimáticas de eficiencia energética para dos tipologías residenciales y un parque en la ciudad de Cartagena de Indias (2020)
Taking into account the basic bioclimatic concepts in the application of the development of architecture, we can observe how the use of the bioclimatic in this, takes great importance due to the problems of thermal and light comfort that we face today in the city of Cartagena, In the search of the improvement of the energy efficiency we focused in developing bioclim atic strategies for two constructed residential typologies and a linear park based on results of analysis and environmental simulations by means of a software of climatic analysis, focus ing in three cases which they are, republican house in the Torices neighborhood stratum 3, apartment of the stratum 5 and linear park of the city of Cartagena in the Crespo neighborh ood, generating a comparative study of the energy consumption of the cases with the presen t conditions versus the application of bioclimatic strategies for the energy efficiency